A numerical study of dynamic capillary pressure effect for supercritical carbon dioxide‐water flow in porous domain. Issue 12 (23rd August 2014) - Das, Diganta B.; Gill, Bhupinder S.; Abidoye, Luqman K.; Khudaida, Kamal J.
<x xml:space="preserve">Abstract</x> Numerical simulations for core‐scale capillary pressure (Pc)‐saturation (S) relationships have been conducted for a supercritical carbon dioxide‐water system at temperatures between 35°C and 65°C at a domain pressure of 15 MPa as typically expected during geological sequestration of CO2. As the Pc‐S relationships depend on both S and time derivative of saturation ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2cn4zdht" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />∂S/∂t</alternatives>) yielding what is known as the "dynamic capillary pressure effect" or simply "dynamic effect, " this work specifically attempts to determine the significance of these effects for supercritical carbon dioxide‐water flow in terms of a coefficient, namely dynamic coefficient (τ). The coefficient establishes the speed at which capillary equilibrium for supercritical CO2 (scCO2)‐water flow is reached. The simulations in this work involved the solution of the extended version of Darcy's law which represents the momentum balance for individual fluid phases in the system, the continuity equation for fluid mass balance, as well as additional correlations for determining the capillary pressure as a function of saturation, and the physical properties of the fluids as a function of temperature. The simulations were carried out for three‐dimensional cylindrical porous domains measuring 10 cm in diameter and 12 cm in height. τ was determined by measuring the slope of a best‐fit straight line plotted between (1) the differences in dynamic and equilibrium capillary pressures <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2cn4zdjc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(Pc, dyn−Pc, equ)</alternatives> against (2) the time derivative of saturation (dS/dt), both at the same saturation value. The results show rising trends for τ as the saturation values reduce, with noticeable impacts of temperature at 50% saturation of aqueous phase. This means that the time to attain capillary equilibrium for the CO2‐water system increases as the saturation decreases. From a practical point of view, it implies that the time to reach capillary equilibrium during geological sequestration of CO2 is an important factor and should be accounted for while simulating the flow processes, for example, to determine the CO2 storage capacity of a geological aquifer. In this task, one would require both the fundamental understanding of the dynamic capillary pressure effects for scCO2‐water flow as well as τ values. These issues are addressed in this article. © 2014 American Institute of Chemical Engineers AIChE J 60: 4266–4278, 2014